INTERAKSI EDUKATIF GURU PAI DALAM MEMBANGUN SIKAP KESALEHAN SOSIAL PESERTA DIDIK DI SD IT NURUL ISLAM - Wasito, Wasito; Afif, Rokhmad; Nursikin, Mukh (IDEALITA: Jurnal Pendidikan dan Sosial Keagamaan, 2022)
The practice of PAI learning which still often focuses on cognitive theoretical issues related to the development of Islamic values ​​by ignoring the development of affective and cognitive-volative aspects, such as the willingness and determination to practice Islamic values, becomes the context for PAI learning. As a result, there is often a disconnect between how religion is understood and how it is practiced in everyday life. Many religious people are individually devout but not socially devout. Further research was conducted on the educative interactions of PAI teachers and their implementation on attitudes. students' social piety based on this problem. This type of research uses qualitative research based on the sociology of education. Observation, interview, and documentation are all methods of data collection. Qualitative analysis of research data includes data reduction, data presentation, verification, and drawing conclusions. Data triangulation, or technical triangulation, sources, and time, serves as a test of research data validation. The findings of this study indicate the following: The first educational interaction pattern used by PAI teachers was a one-way interaction pattern. PAI teachers use the lecture method to apply this one-way interaction pattern. 2) Two-way interaction patterns, which are carried out through a question and answer format by PAI instructors. 3) PAI teachers use group discussion learning methods and various religious activities related to social piety as part of the learning process. of the multidirectional interaction pattern. Second, the PAI KBM process is used to implement educative interactions for PAI teachers at SD IT Nurul Islam Tengaran, including getting students to pray first. and after learning, understanding previous learning materials, mastering and delivering good learning materials, connecting with community issues, creating a pleasant learning environment with the help of media and learning strategies, being open, inclusive, objective, and non-discriminatory towards students, and provide an evaluation to measure students' understanding of the learning material. Outside of KBM PAI, namely introducing students to Islamic teachings, instilling values ​​through school-based religious activities.